A comparative study on the hepatoprotective action of bear bile and coptidis rhizoma aqueous extract on experimental liver fibrosis in rats - Wang Ning; Feng Yibin; Cheung Fan; Chow Oi-Yee; Wang Xuanbin; Su Weiwei; Tong Yao (BMC, 2012)
Abstract Aim of the study Bear bile and Coptidis Rhizoma have been used in Chinese medicine with a long tradition in treating heat-diseases. Both bear bile and Coptidis Rhizoma are used to treat liver diseases in clinical practice of Chinese Medicine. Since bears are currently endangered, it raises the question whether the use of bear bile is ethical. To look for substitute for bear bile, the aim of this study is to compare the anti-fibrotic effects of Coptidis Rhizoma and its major component berberine with the actions of bear bile and its major compound tauroursodeoxycholic acid on experimental liver fibrosis in rats. Method Quality assessment was conducted with high performance liquid chromatography. The experimental liver fibrosis in rats was induced by carbon tetrachloride, alcohol, and bile duct ligation respectively. The biochemical criteria in the blood and tissue samples were measured to evaluate the anti-fibrotic properties and underlying mechanisms of the drugs. Results Coptidis Rhizoma Aqueous Extract (CRAE), berberine, and bear bile exerted anti-fibrotic properties on various liver fibrosis models in rats. CRAE and berberine significantly reduced the peroxidative stress in liver through increasing the superoxide dismutase enzyme activity. CRAE and berberine were able to excrete bilirubin products from the liver and protect hepatocytes from cholestatic damage. The effect of CRAE and berberine are comparable to that of bear bile. Conclusion Instead of using bear bile, CRAE and berberine can be potential substitutes in treating liver fibrosis.